IMPLEMENTASI PROGRAM PENDIDIKAN YANG DIINDIVIDUALKAN (PPI) DI SD INKLUSIF DI WILAYAH JAKARTA SELATAN - Siti Masyithoh (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
This study aims to describe the implementation of the Individualized Education Program in Inclusive Elementary Schools in South Jakarta. The research method used is a descriptive qualitative research that is casuistic in nature at SDN 01 Lebak Bulus and SDN 02 Lebak Bulus in South Jakarta. The subjects in this study were principals, teachers and students with special needs. In this study, the researcher used several instruments, namely document studies, interviews and observations that were used in various ways which were also used to measure the level of validity of the data through the triangulation process. The samples of this study were teachers, principals, and students in 2 (two) inclusive elementary schools  in South Jakarta, namely SDN 01 Lebak Bulus and SDN 02 Lebak Bulus. The results showed that the recruitment of Special Advisor Teachers from graduates of Special Education had been carried out at SDN 01 and 02 Lebak Bulus, South Jakarta. However, the 95% Individual Education Program could not be implemented in these schools due to the absence of a legal protection that protects the rights of Special Guiding Teachers so that they cannot provide proper academic services to students with special needs. Teachers who were originally recruited to become Special Guidance Teachers were turned into classroom teachers in regular classes. As a result, students with special needs cannot be served properly and their learning achievement becomes retarded. Self-development and self-development for these students also cannot be carried out because of the clash of funds and human resources.